2013
DOI: 10.1007/s12311-012-0436-9
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Human Procedural Learning by Cerebellar Transcranial Direct Current Stimulation

Abstract: Neuroimaging studies suggest that the cerebellum contributes to human cognitive processing, particularly procedural learning. This type of learning is often described as implicit learning and involves automatic, associative, and unintentional learning processes. Our aim was to investigate whether cerebellar transcranial direct current stimulation (tDCS) influences procedural learning as measured by the serial reaction time task (SRTT), in which subjects make speeded key press responses to visual cues. A prelim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
151
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(171 citation statements)
references
References 51 publications
16
151
3
1
Order By: Relevance
“…There was no difference in subjective ratings between the two stimulation groups, and the effects of stimulation were apparent the next day, which is unlikely to be a nonspecific enhancement of attention or arousal. This result is similar to other research indicating that the effects of tDCS are better observed at a delay [35,39,52] and to Study 1 in that no differences between the sham and anodal group were observed on the same day. It is possible that the aftereffect of cerebellar tDCS, which can last for up to 30 min after stimulation is over [33], could be directly enhancing consolidation processes.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…There was no difference in subjective ratings between the two stimulation groups, and the effects of stimulation were apparent the next day, which is unlikely to be a nonspecific enhancement of attention or arousal. This result is similar to other research indicating that the effects of tDCS are better observed at a delay [35,39,52] and to Study 1 in that no differences between the sham and anodal group were observed on the same day. It is possible that the aftereffect of cerebellar tDCS, which can last for up to 30 min after stimulation is over [33], could be directly enhancing consolidation processes.…”
Section: Discussionsupporting
confidence: 91%
“…These results together might suggest that cathodal stimulation does not lead to the exact behavioural inverse of anodal tDCS [49], and might depend on characteristics of the task. Differences in task or stimulation protocol may also explain the lack of effects of anodal tDCS on total learning during practice or sequence-specific learning, which was not consistent with the enhanced learning that Ferrucci et al [39] observed after anodal tDCS was applied after the baseline SRT task. We stimulated during practice of the sequences whereas they stimulated between two sessions of SRT task performance.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Procedural learning assessed by the serial reaction time test (SRTT) can be improved in healthy adults by cerebellar TDCS [81,83].…”
Section: The Non-motor Role Of the Cerebellum In Dystoniamentioning
confidence: 99%